What constitutes our right to belong? - Walter Lorenz (Social Work & Society, 2020)
As the manuscript of a dinner speech, this chapter questions light-heartedly whether having the right to belong to a social occasion, such as a conference dinner, bears a relationship with social policy criteria that constitute "belonging" to a social and political unit such as the nation state as welfare state. Since the criteria that constituted the "classical" welfare regimes, and hence the meaning of what is "social", are currently under attack from neoliberal's insistence on individual self-care, the talk seeks to show that the splitting of the meaning of "social" into a derogatory ("social cases") and a sentimental ("social benefactor") orientation impacts on all forms of "socialising" by rendering them instrumental for ulterior motives rather than communally enjoyable.